Towards a Political Philosophy of the Environmental Crisis and Climate Change - Quesada Rodríguez, Francisco (2024)
This article integrates ecology and environmental ethics to find a new political philosophy that addresses the challenge of the environmental crisis. Although ecology as a science allows us to understand the state of the environment, ethics and politics must be integrated into a new environmental democracy that systematically responds to the challenge of climate change. The epistemological demarcation of science, philosophy and politics based on the ecological question, presented by environmental thinkers, helps organize democracy so that citizens can actively participate in political decision-makingabout the environment.